DIAGNOSIS OF DAMP AND STRUCTURAL PATHOLOGIES IN A SAMPLE OF MUD HOUSES USING 3D SCANNING. CASE STUDY: A HOUSE IN THE KHANGUET SIDI NADJI KSAR, BISKRA, ALGERIA - Khalissa Hamel; Manel Nasri; Faten Ghanemi; Soumaya Makhloufi; Fouzia Meliouh; Kebbour Akram (International Journal of Innovative Technologies in Social Science, 2024)
Raw earth architecture is an important part of Algeria’s cultural heritage, especially in arid and desert regions. These historic settlements, inhabited since the Middle Ages, have enabled people to survive in difficult conditions. However, these centres are now abandoned and neglected by their inhabitants, who prefer more modern lifestyles. The Ksar of Khanguet Sidi Nadji in Biskra, a fortified urban settlement, is renowned for its rich historical heritage and exceptional architectural beauty. Classified as a natural heritage site in 1968, the ksar is facing gradual deterioration and increasing abandonment, mainly due to the intrinsic fragility of the mud buildings, structural problems and various pathologies. These deteriorations are exacerbated by the passage of time and human impacts, leading to premature ageing of the buildings, a lack of maintenance and the abandonment of certain structures that have become obsolete. The aim of this article is to undertake an in-depth investigation of the pathologies affecting adobe architecture, using the 3D digital survey technique. The study will focus on a specific building (House 10) located in the ksar of Khanguet Sidi Nadji, selected from a representative sample. The in situ survey will be carried out in close collaboration with experts in the pathology of mud constructions, and will be supplemented by analyses carried out using specialist tools. This scientific approach will enable us to establish a precise diagnosis, which is a prerequisite for the rehabilitation of this endangered architectural heritage. It will also ensure rigorous traceability, while promoting the use of raw earth as a sustainable building material.